2019
DOI: 10.3389/fpsyt.2019.00120
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Compulsory Re-admission to Psychiatric Inpatient Care

Abstract: Objective: This prospective study addresses risk factors of compulsory re-admission focusing on the role of the patient's subjective symptom distress and perceived social support, based on comprehensive patient and external (clinicians, study staff) assessments. Methods: Of the baseline sample, 168 (71%) patients with serious mental disorders, who had been compulsorily admitted to psychiatric inpatient care, were followed over 24 months after discharge within the framework of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…We also found that two-thirds of second ECPAs (66.1%) occurred within 6 months of the first. This is similar first to the findings of Lay et al, who reported a peak of compulsory readmissions shortly after discharge; 10 and also to the findings of van der Post et al, who reported a higher risk of readmission in the first year after discharge than in the subsequent follow-up years. 8 However, in the first year of follow-up, the study by Lin et al showed relatively low rates of compulsory readmissions.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We also found that two-thirds of second ECPAs (66.1%) occurred within 6 months of the first. This is similar first to the findings of Lay et al, who reported a peak of compulsory readmissions shortly after discharge; 10 and also to the findings of van der Post et al, who reported a higher risk of readmission in the first year after discharge than in the subsequent follow-up years. 8 However, in the first year of follow-up, the study by Lin et al showed relatively low rates of compulsory readmissions.…”
Section: Resultssupporting
confidence: 91%
“…Our findings with regard to history of mental healthcare and age are similar to those in the other studies, in which younger age and an existing treatment history in mental healthcare were consistently identified as important risk factors for repeated ECPAs. [8][9][10] Our findings with regard to various factorslevel of self-care, housing problems and lower GAF scoresalso indicate that patients with severe mental illnesses 14,15 who show lower level of functioning are particularly susceptible to repeated compulsory psychiatric admissions. This, too, is in accordance with the literature on revolving-door patients.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Leaving hospital often leads to the re-emergence of the pre-existing stressors that contributed to admission [ 23 , 24 ]. This may explain why the risk of relapse and rehospitalization immediately postdischarge is high [ 25 ]. Rates of suicide among patients in their first 3 months after discharge are also high, estimated at 100 times the global suicide rate, with a particular risk in the first week after discharge [ 23 ].…”
Section: Introductionmentioning
confidence: 99%